2003
DOI: 10.1016/s1097-2765(03)00090-x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic, Proteasome-Mediated Turnover of Unliganded and Liganded ERα on Responsive Promoters Is an Integral Feature of Estrogen Signaling

Abstract: We present an integrated model of hERalpha-mediated transcription where both unliganded and liganded receptors cycle on estrogen-responsive promoters. Using ChIP, FRAP, and biochemical analysis we evaluate hERalpha at several points in these cycles, establishing the ubiquitination status and subnuclear distribution of hERalpha, its mobility, the kinetics of transcriptional activation, and the cyclic recruitment of E3 ligases and the 19S regulatory component of the proteasome. These experiments, together with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

62
618
5
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 677 publications
(693 citation statements)
references
References 44 publications
62
618
5
8
Order By: Relevance
“…Linkage between PR hyperactivity and PR turnover (Fig. 4B) suggests that such complexes likely contain ubiquitin E3 ligases, as has been shown for activated ER (45). We reported that both PR downregulation and PR transcriptional synergy in the presence of MEKK1 and progestins were similarly blocked by inhibitors of p42/p44 MAPKs (PD98059 or UO126), the 26S proteasome (lactacystin), or nuclear export (leptomycinB) (14,15).…”
Section: Functions Of Liganded Prsupporting
confidence: 66%
“…Linkage between PR hyperactivity and PR turnover (Fig. 4B) suggests that such complexes likely contain ubiquitin E3 ligases, as has been shown for activated ER (45). We reported that both PR downregulation and PR transcriptional synergy in the presence of MEKK1 and progestins were similarly blocked by inhibitors of p42/p44 MAPKs (PD98059 or UO126), the 26S proteasome (lactacystin), or nuclear export (leptomycinB) (14,15).…”
Section: Functions Of Liganded Prsupporting
confidence: 66%
“…ChIP-seq experiments in MCF-7 cells have shown binding of ERα to a significant number of estrogen target sites after 1 h of ICI 182,780 treatment (Welboren et al . 2009); in contrast, association of ERα with DNA was not observed 3 h after addition of ICI 182,780 in another study (Reid et al . 2003), possibly due to receptor degradation.…”
Section: Impact Of Ae-induced Erα Conformation On Cofactor Recruitmenmentioning
confidence: 91%
“…2015 and refs within); some of these proteins are recruited to DNA and can act as ERα coactivators (Lonard et al . 2000, Reid et al . 2003).…”
Section: Role Of Post-translational Modifications Of Erα By Ubi-like mentioning
confidence: 99%
“…The primary genomic sensor for many dietary and environmental (e.g. xenobiotic) factors is the nuclear receptor superfamily of ligand-activated transcription factors, which bind steroid hormones, vitamin micronutrients and macronutrients such as fatty acids, lipids and bile acids (26)(27)(28)(29) .…”
Section: The Complex Aetiology Of Cancermentioning
confidence: 99%